Influence of the Relational Context on Reproductive Coercion and the Associated Consequences - Lévesque, Sylvie (Violence against women, 2021)
Reproductive coercion (RC) refers to behaviors that interfere with contraception use or pregnancy and that limit reproductive autonomy. This article presents the results of a qualitative exploratory study of 21 young women in Canada who experienced RC perpetrated by an intimate partner along with the associated consequences. Results reveal that nonconsensual condom removal occurred more often in uncommitted relationships without violence, whereas pressure to become pregnant and pregnancy coercion occurred more often in committed relationships where other forms of violence were also present. Participants reported numerous repercussions on their psychological, sexual, and reproductive health and on their emotional and relational well-being.